Combined Metabolome and Transcriptome Analyses of Young, Mature, and Old Rhizome Tissues of Zingiber officinale Roscoe - Liu, Huanfang; Yang, Honghua; Zhao, Tong; Lin, Canjia; Li, Yongqing; Zhang, Xinhua; Ye, Yushi; Liao, Jingping (Frontiers in Genetics, 2021)
Ginger (Zingiber officinale Roscoe) is known for its unique pungent taste and useability in traditional Chinese medicine. The main compounds in ginger rhizome can be classified as gingerols, diarylheptanoids, and volatile oils. The composition and concentrations of the bioactive compounds in ginger rhizome might vary according to the age of the rhizome. In this regard, the knowledge on the transcriptomic signatures and accumulation of metabolites in young (Y), mature (M), and old (O) ginger rhizomes is scarce. This study used HiSeq Illumina Sequencing and UPLC-MS/MS analyses to delineate how the expression of key genes changes in Y, M, and O ginger rhizome tissues and how it affects the accumulation of metabolites in key pathways. `The transcriptome sequencing identified 238,157 genes of which 13,976, 11,243, and 24,498 were differentially expressed (DEGs) in Y vs M, M vs O, and Y vs O, respectively. These DEGs were significantly enriched in stilbenoid, diarylheptanoid, and gingerol biosynthesis, phenylpropanoid biosynthesis, plant-hormone signal transduction, starch and sucrose metabolism, linoleic acid metabolism, and α-linoleic acid metabolism pathways. The metabolome profiling identified 661 metabolites of which 311, 386, and 296 metabolites were differentially accumulated in Y vs M, Y vs O, and M vs O, respectively. These metabolites were also enriched in the pathways mentioned above. The DEGs and DAMs enrichment showed that the gingerol content is higher in Y rhizome, whereas the Y, M, and O tissues differ in linoleic and α-linoleic acid accumulation. Similarly, the starch and sucrose metabolism pathway is variably regulated in Y, M, and O rhizome tissues. Our results showed that ginger rhizome growth slows down (Y>M>O) probably due to changes in phytohormone signaling. Young ginger rhizome is the most transcriptionally and metabolically active tissue as compared to M and O. The transitioning from Y to M and O affects the gingerol, sugars, linoleic acid, and α-linoleic acid concentrations and related gene expressions.